Palermo, criminal capital of Italy (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
After the Second World War, although Rome remained the political capital of Italy, Palermo took on a dominant role as the 'criminal' capital, concentrating mafia and business power, especially between the 1970s and 1990s. Mafia-style organized crime, fuelled by drug trafficking, gained increasing influence on a national scale, with Palermo as the epicentre of a criminal network that progressively involved finance, politics, economic crime, and deviant Freemasonry. The Sicilian city became, in fact, a place where legal and illegal businesses intertwined, pushing its dynamics to expand far beyond regional borders, even influencing Milan, the country's economic capital. The importance of Palermo emerged not only in the management of illicit trafficking but also in its connections with powerful financial and political circles. From this, it is clear that Palermo played the role of a center of control and alternative regulation compared to Rome.
Keywords: criminal capital; integrated criminal network; convergence; concentration of power; criminal violence